Queries on medication use during pregnancy: characterisation of the Swiss Teratogen Information Service database (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: Limited information on medication safety may result in concerns on how to treat pregnant and breast-feeding patients. The Swiss Teratogen Information Service (STIS) provides information to healthcare professionals about medications during pregnancy and breast feeding. Our objective was to describe the queries addressed to the STIS over the past two decades.METHODS: The STIS maintains a database of queries on pregnancy outcomes after exposure to various substances, which may be a valuable source of information. We initially analysed the general characteristics of all queries. Thereafter, we focused on exposure to medications during singleton pregnancies and associated health-related aspects.RESULTS: From 2000 to 2019, 7148 queries were entered into the database. An increasing number of queries was recorded over the study period, with an average of 357 queries entered into the database per year. Most of the enquirers were physicians; more specifically, gynaecologists/obstetricians (2389/7148; 33.4%) and psychiatrists (1007/7148; 14.1%). Two thirds (4747/7148; 66.4%) of the queries addressed medication intake during pregnancy; the next most frequent queries concerned planned medication in the context of pregnancy (928/7148; 13.0%) or medication use during breast-feeding (873/7148; 12.2%). In more than 50% (3611/7148) of cases, women were treated with more than one drug; altogether, 15193 medications (taken alone or in combination) were identified. The most frequent queries concerned medicines for the nervous system (ATC group N, n = 7042), with selective serotonin reuptake inhibitors (n = 1271) in the leading position, followed by benzodiazepine derivatives (n = 1102) and other antidepressants (n = 780). The next most frequently mentioned drug classes were anti-infectives for systemic use (J, n = 1586) and drugs for the alimentary tract and metabolism (A, n = 1205). Analysis of follow-up information on cases of medication exposure during singleton pregnancies (n = 2672) revealed an offspring malformation rate of 4.2%. The organ system most often affected was the musculoskeletal system, followed by the circulatory system; congenital malformations of the nervous system and chromosomal abnormalities were also seen. The three most frequently documented congenital diagnoses were malformations of cardiac septa, the brain and major arteries.CONCLUSIONS: Healthcare professionals often have concerns regarding the treatment of pregnant women with medication, and require professional counselling in this area. A variety of drugs are mentioned in queries addressed to the STIS, of which psycholeptics and psychoanaleptics are the most frequent. Proper guidelines on their use during pregnancy appear particularly urgent.